2015
DOI: 10.4317/medoral.20652
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study maxillofacial fractures epidemiology and treatment plans in Southeast of Iran

Abstract: BackgroundThe epidemiology of facial injuries varies in different countries and geographic zones. Population concentration, lifestyle, cultural background, and socioeconomic status can affect the prevalence of maxillofacial injuries. Therefore, in this study, we evaluated the maxillofacial fractures epidemiology and treatment plans in hospitalized patients (2012-2014) which would be useful for better policy making strategies.Material and MethodsIn this retrospective study, the medical records of 386 hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
56
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 50 publications
10
56
1
9
Order By: Relevance
“…The results showed that the highest prevalence of facial trauma is in men, as shown in other studies [2][3][4][5][6][7][8][9][10][11][12]. The most affected age group was 18 to 40 years (young adult stage), corresponding to 67.4%.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The results showed that the highest prevalence of facial trauma is in men, as shown in other studies [2][3][4][5][6][7][8][9][10][11][12]. The most affected age group was 18 to 40 years (young adult stage), corresponding to 67.4%.…”
Section: Discussionsupporting
confidence: 69%
“…Motorcycle accidents as cause of facial trauma were also the most prevalent in the study by Silva et al [11], being responsible for 44% of all cases. However, the literature has reported a gradual change in the etiology of facial fractures, with interpersonal violence overcoming the vehicles accident as the most common cause [3][4][5][6][7][8][9][10][11][12][13][14][15]. Although in recent years many traffic policies have been instituted aiming a greater safety in public roads [16], many laws, such as the compulsory use of helmets and driver's licenses, are not respected in small towns that prevail in the Jequitinhonha valley.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority (24.8%) of injuries were due to two wheeler vs two-wheeler accidents, 20.9% of injuries are due to selffall/skid, 19% of injuries by two wheelers met accidents with four wheelers and had poly trauma, 18.7% of accidents by pedestrians crossing, and 16.7% by animal crossing. Samieirad et al 20 reported that left injuries were common next to bilateral injuries. Das et al, 8 Chakranarayan et al 9 reported…”
Section: Discussionmentioning
confidence: 99%